WANPRESTASI DALAM PERJANJIAN JUAL BELI KACAMATA ANTARA PENJUAL DAN PEMBELI DI OPTIK CITRA PEKANBARU - Vertina, Annisa Sophia; Bachtiar, Maryati; Hasanah, Ulfia; Hanifah, Mardalena (Jurnal Pahlawan, 2024)
In the implementation of the sale and purchase agreement at Optik Citra Pekanbaru, there were several buyers who committed default so that the seller suffered losses due to the actions of the buyer. This study is a sociological legal research. Research results First, the sale and purchase agreement between the seller and the buyer at Optik Citra Pekanbaru was carried out verbally and in writing. The verbal agreement of the goods to be ordered and the price to be paid and the written agreement written in the payment note and in the note explained the date when the goods were ready to be picked up and the remaining bill. Second, a number of buyers did not complete the bill and pick up the goods that had been ordered and there was a default by the buyer to the seller so that the form of settlement carried out was non-litigation or out of court and accepted a number of losses. Keywords: Wanprestasi, Agreement, Sale and Purchase